Teaching Learning Process In Bilingual Class For Eighth Grade Students At SMP N 1 Sine Ngawi In 2012/2013 Academic Year - Pratama, Hanggara Putra; , Aryati Prasetyarini, S.Pd; , Siti fatimah, S.Pd, M.Hum (2013)
This research aims at describing the teaching-learning process at eighth grade students of SMP N 1 Sine in 2012/2013 academic year. It is conducted to describes the implementation of bilingualism in teaching-learning process, the percentage of teacher in using English, and problem faced by the teacher in the eighth grade bilingual program students of SMP Negeri 1 Sine Ngawi. The object of the study is the teaching learning process in eighth grade bilingual class of SMP Negeri 1 Sine, at 2012/2013 academic year. The subject of the study is the English, Mathematics, Physics teachers and Bilingual program students at SMP Negeri 1 Sine, at 2012/2013 academic year. The method of collecting data are observation, interview, and document analysis. In analyzing data the writer applied descriptive qualitative research consisting of data reduction, presenting the data, and drawing conclusion. The result of the study show the model of teaching-learning activities is Bilingual method in the classroom techniques used are: Peer Group, Question and answer, Task - based or Experiential Learning, Graphics Organizer. In teaching learning process the teacher delivers and explains the material to the students' use 40% in English and 60% in Indonesian. The problems faced by the teacher in teaching learning process are the limited capability of the teacher in English mastery, Different background knowledge among the students, and Inactive students in teaching learning process which is make the students do not understand the material given.